Penerapan Pembelajaran MEA (Means-End Analysis) Berbantuan Schoology Untuk Meningkatkan Hasil Belajar Matematika - Sudarman, Satrio Wicaksono; Linuhung, Nego (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The low learning outcomes of students, because they have difficulty in solving the problems given, especially trigonometry material and the lack of interest of students in participating in the mathematics learning process. In addition, teachers and students have not utilized information technology optimally, so efforts are needed to improve student learning outcomes by applying MEA (Means-End Analysis) learning. The research subjects were all class VIII students of SMA Negeri 1 Pekalongan in the 2018/2019 academic year. Research sample is class XI b, which amounted to 22 students. The purpose of this classroom action research to determine the increase in learning outcomes of students who get the MEA (Means-End Analysis) learning model assisted by Schoology. Based on the results of the class action research conducted and the discussion that has been described, it can be concluded that the MEA (Means-End Analysis) learning model assisted by Schoology can improve the learning outcomes of class XI students of SMA Negeri 1 Pekalongan in the 2018/2019 Academic Year. Learning outcomes have increased from pre-survey to cycle I wherein the survey that is 31,82% to 45,45%, students who are thoroughly studied have increased by 13,63%. in cycle II the learning outcomes of students increased from Cycle I is 45,45% to 95,45%, students who have completed learning have increased by 50%.Keywords: learning MEA (Means-End Analysis), Schoology, learning outcomes